The Influence of Entrepreneurship Learning on the Readiness of Entrepreneurship Students to Become Successors in Family Business - Khazanah, Latifah; Yanwar, Choirul Umam; Rizkiyadi, Aldi Alfa; Savitri, Raissa Risty; Fauziyah, Azizah (CV. Tripe Konsultan, 2024)
Succession is the most important thing in the sustainability of a family business. The transfer of family business management from the first generation to the next generation has an impact on the performance and development of the business. This study aims to analyze the extent to which entrepreneurial learning influences successor readiness in family businesses, so the identification in this study is as follows: What is the picture of the readiness of potential successors and the influence of entrepreneurial learning and How does entrepreneurship learning influence readiness to become a successor in a family business?This study uses a quantitative method with a quantitative descriptive approach. The population in this study was aimed at students of the Indonesian Education University, Tasikmalaya Campus, Entrepreneurship Study Program with a purposive sampling technique with the provision that they have a family business, so that the sample obtained was 30 respondents. Based on the results of the research conducted by researchers regarding the influence of entrepreneurial learning on the readiness of successors in family businesses, it shows positive results, meaning that there is a positive influence of entrepreneurial learning on the readiness of prospective successors. This can be seen from each indicator that is related to each other, which indicates that the better the entrepreneurial learning, the better the readiness of successors, conversely, if there is a lack of entrepreneurial learning, it can affect the lack of readiness of successors in family businesses.